Mixed Reality System for Ergonomic Assessment of Driver's Seat - Caruso, Giandomenico (International Journal of Virtual Reality, 2011)
Virtual Reality techniques are more and more used to validate the design hypotheses during different phases of the product development. In the automotive field, however, there are some types of analyses that are unlikely to be performed by using only a Virtual Prototype (VP) of the vehicle. Therefore, the trend is to develop systems -called seating bucks- that enable engineers to integrate virtual and real objects to provide a tangible interface for the VP of the vehicle. This research aims at defining a new system and an evaluation protocol to improve, simplify and speed up the usual activities carried out for the ergonomic assessment of the driver's seat. In particular, we are interested in evaluating the ergonomics of car's dashboard with its knobs, buttons, display and other control systems. In this paper, we have described the development of this system by providing useful information about the physical issues, related to the seating buck structure, and about the development of the MR environment. The system and the evaluation protocol have been validated by performing several testing sessions with users. The tests confirm the effectiveness of our approach and have enabled us to achieve at interesting considerations.